34. Oops, I Didn't Follow My Post Vaccinaton Instructions. (31st December 2020) - Manandhar, Sabina; Ramsey, Keith; Buffaloe, Valerie
Abstract: Background: Smallpox vaccine is derived from vaccinia virus, a large, double-stranded DNA virus. With the worldwide eradication of smallpox, routine vaccination with vaccinia virus is no longer performed. However, at-risk laboratory and health care personnel continue to be vaccinated against smallpox, and large numbers of military personnel in the United States resumed smallpox vaccination after the anthrax bioterrorism in 2001. Two available smallpox vaccines are part of the strategic stockpile in the United States; one is a replication-deficient modified vaccinia Ankara vaccine (MVA), and the other is a replication-competent smallpox vaccine (ACAM2000). Among others, one of the potential complications of smallpox vaccine is an accidental autoinoculation or accidental inoculation of close contacts. Methods: A 27-year-old female presented to the employee health clinic at Vidant Medical Center with a 7-day lesion on her right upper extremity. She denied any fever, chills, pets at home, insect bites or trauma to the area. She was using inhaled nebulizers for her asthma and lived in Greenville, NC, with her boyfriend. The lesion was non itchy, approximately 5 mm blister like rash that ulcerated with a grayish, white center and had a surrounding red border. On further questioning, she disclosed that her boyfriend was a marine, who was recently vaccinated against smallpox two weeks before she developed the skin lesion, but he did not cover the site as instructed. Her lesion was unroofed and a sample was collected and sent to NC State Laboratory of Public Health for identification. It was also reported to the NC State Department of Health for possible contact transmission of smallpox. In the meantime, the patient was instructed to cover the area while at work, keep the lesion open to air at home, and avoid skin-to-skin contact. Initial Lesion Lesion after Unroofing Results: The sample returned positive for Orthopoxvirus DNA by PCR. Conclusion: Recipients of smallpox vaccine have a potential for autoinoculation and inoculation of close contacts. Hence, the vaccine recipients should be well educated about proper care of the vaccination site for preventing possible contact transmission of the virus. These include covering the vaccination site, proper hand washing after bandage changes, and avoiding skin-to-skin contact. Disclosures: All Authors : No reported disclosures